UPAYA MENINGKATKAN KINERJA ORGANISASI PEMERINTAH MELALUI PENGIMPLEMENTASIAN KONSEP ’SIX SIGMA - Listiani1, Teni (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
Six Sigma Program was firstly applied and developed by Motorola Corporation. Six Sigma is a program focused on the massive and continous quality improvement. Through the principles, measurement, and phase of this Six Sigma Program, the performance of organization (either in Private or in Government) is able to develop and improve. To some of Government organizations in which the performance and quality of the service are still generally considered dissatisfied, the improvement in every essential aspect of the organization is of importance. Six Sigma is an alternative for the government organization that expects to improve and develop the performance. The early phase in applying Six Sigma should be initiated by a strong commitment and motivation of the Top Leaders to implement the improvements in every organization. Then, Six Sigma Program can be applied throug DMAIC (Define, Measure, Analyze, Improve, Control) on the characteristic of the quality of the stakeholders need.